Assessment of the feed additive consisting of sodium benzoate (Protural®) for weaned piglets for the renewal of its authorisation and the extension of use to other growing Suidae (Taminco Finland Oy) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (Wiley, 2021)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Protural® (sodium benzoate) when used as a zootechnical additive in feed for weaned piglets and other growing Suidae at 4,000 mg/kg feedingstuff. Protural® consists of sodium benzoate without any carrier materials and is currently authorised for use in weaned piglets. This opinion concerns the renewal of the authorisation of Protural® for weaned piglets and the evaluation of the new use in other growing Suidae. The applicant provided evidence that the additive currently in the market complies with the existing conditions of authorisation. The FEEDAP Panel concluded that Protural® is safe under the current conditions of authorisation for the target species, consumers of products from animals fed the additive and the environment. Protural® was not considered as irritant to skin and eyes but a skin sensitiser. Based on dusting potential data, the FEEDAP Panel considered that the powder formulation of the additive represented a risk by inhalation. There was no need for assessing the efficacy of Protural® in the context of the renewal of the authorisation for weaned piglets. The efficacy data previously evaluated allowed the FEEDAP Panel to conclude that the additive has the potential to be efficacious at the level of 4,000 mg/kg feedingstuff in other growing Suidae. A conclusion cannot be reached for the efficacy in pigs for fattening.